2017
DOI: 10.1016/j.diabres.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness, fatness and incident diabetes

Abstract: High CRF has a stronger protective effect on diabetes among obese than among normal weight men, supporting the recommendation of fitness-enhancing physical activity for preventing diabetes among the obese.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…The literature search yielded a total of 8,189 unique articles (Figure ). After titles and abstracts were screened and upon full‐text review considering the reasons for exclusion listed in Figure , 15 studies met the inclusion criteria for this meta‐analysis . Notably, two of them were from the Coronary Artery Risk Development in Young Adults Study , two were from the Tokyo Gas Study , and two were from the Aerobics Center Longitudinal Study enrolling only men ; however, they reported different outcomes of interest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature search yielded a total of 8,189 unique articles (Figure ). After titles and abstracts were screened and upon full‐text review considering the reasons for exclusion listed in Figure , 15 studies met the inclusion criteria for this meta‐analysis . Notably, two of them were from the Coronary Artery Risk Development in Young Adults Study , two were from the Tokyo Gas Study , and two were from the Aerobics Center Longitudinal Study enrolling only men ; however, they reported different outcomes of interest.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to being able to predict the risk of all‐cause and disease‐specific mortality , a large body of literature indicates that CRF might be associated with the risk of type 2 diabetes . However, the findings on the magnitude of risk reduction in relation to higher levels of CRF are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical activity (PA) is a health behavior promoted to all individuals because of its preventive relationship with disease [1,2,3,4,5], its positive relationship with longevity [6,7,8,9,10], and its ability to enhance health-related quality of life (HRQOL) [11,12,13,14]. Cardiorespiratory fitness (CRF) is a trait possessed by individuals, characterized by the ability to engage in dynamic exercise of at least moderate intensity for prolonged periods [15], and is also related to positive health outcomes [16,17,18,19,20]. Obesity is a growing concern world-wide [21] with health promotion efforts directed toward increasing PA and modifying diet [22,23,24].…”
Section: Introductionmentioning
confidence: 99%